The stigma experiences and perceptions of families living with epilepsy: Implications for epilepsy-related communication within and external to the family unit. Issue 9 (September 2016) - Benson, Ailbhe; O'Toole, Stephanie; Lambert, Veronica; Gallagher, Pamela; Shahwan, Amre; Austin, Joan K.
Highlights: There is a well-documented association between epilepsy and stigma. Epilepsy-related stigma may be associated with how families communicate about epilepsy. We assessed the relationship between epilepsy-related stigma and family communication. Higher child/parent stigma perceptions are associated with greater epilepsy concealment. Health professionals should assist families to engage in epilepsy-related dialogue. Abstract: Objective: This paper presents the stigma experiences of children with epilepsy (CWE) and their parents and outlines the relationship between CWE's and parents' stigma perceptions, demographic and seizure variables, and epilepsy-related communication within and external to the family. Methods: A mixed-method design was employed. In phase one, 33 CWE and 40 parents participated in qualitative interviews. In phase two, 47 CWE and 72 parents completed a cross-sectional survey. Results: CWE and their parents experience felt and enacted stigma via social exclusion, activity restriction, teasing/bullying, internalised negative feelings to epilepsy, concealment of epilepsy and parental stigma-coaching. Higher CWE and parent stigma perceptions were significantly correlated with greater epilepsy concealment from others outside the family and greater negative affect around epilepsy-related communication within the home. Conclusion: As CWE and their parents grapple with epilepsy-related stigma they may inadvertently contribute to the silence encircling epilepsy through diagnosis concealment, stigma-coaching and/or by engaging in limited family dialogue about epilepsy. Practice implications: Healthcare professionals need to be cognisant of broaching the sensitive topic of epilepsy-related stigma during their engagements with families living with epilepsy. Assisting families to appropriately engage in dialogue surrounding epilepsy is likely to improve the psychosocial wellbeing of CWE and their parents.